The Teaching Strategies to Deal with Students’ Misbehaviors in Dangerous Minds Movie - Dinni Mawaddah (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2022)
The teacher's responsibility is not only increases student intelligence but also the responsibility for building student morale. This study aims to identify students' misbehaviors and how teachers' strategies in dealing with them are found in the Dangerous Minds movie. In identifying student's misbehavior, researcher used Charles's theory. This research uses qualitative research methods. The way to collect data was by observing the movie. And the research instrument used was observation sheet. The types of misbehavior such as apathy, needless talk, annoying others, disruption, aggression and fighting, and defiance of authority was found in this movie. And the strategies used such as teach karate to attract students' attention, bring students to the amusement park, give snacks or candies when students succeed in answering questions, go to the house of the child involved in the fight and tell their parents that this is not their fault and praise the students, presenting a lavish dinner to a group that wins the Dylan-Dylan Contest, and protect students who are threatened with murder. And finally, with great effort, the strategies used by Mrs. Johnson to deal with student's misbehaviors were successful.